(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2018)
Astronomical pictures spread in recent decades by the space agencies have shaped our imagery of the cosmos. Because of their brightness, brilliant colours, breath–taking composition and technological content they may appear self–evident and may suggest the idea of an objective, truthful representation. Nevertheless the real subject of these images often remains ambiguous. Advanced images processing techniques translate data in pictures that sometimes don’t have an evident scientific content and utility, created with the specific purpose of stimulate an aesthetic and emotional response in the public. The comparison between rough data from telescopes and these evocative “digital paintings” shows their relationship with the history of landscape painting and photography and the panorama’s tradition of mise en scene of the nature. Therefore they question the traditional relationship between reality, vision and landscape. These issues stimulated a debate involving scientists, art historians, and visual studies scholars. Specific researches have highlighted the connections between these images and the sublime (Kessler 2012), their relationship with art and science (Kemp 2006), the question of their legitimacy and truthfulness (Elkins 2008). Starting from the state of the art, this work looks at these controversial representations of the faraway space in the aim: to investigate their meaning and role and understand why spacescapes often communicate such a sense of familiarity despite their unfamiliar subjects; to highlight some links with the European art tradition and to investigate the connections with the sublime and the picturesque, both in their historical and contemporary expressions; to propose some considerations about the relationship between these pictures, reality and truth and about their role in the contemporary visual culture.